Answer

Verified

415.5k+ views

**Hint:**The given problem is pretty easy and you can solve it in a few steps. Here, you can use the concept of limits and you will let a condition that when x=a, then assume the form as$\dfrac{0}{0}$. So, let’s see how we can solve the given problem.

**Step-By-Step Solution:**

The given problem statement is we need to evaluate$\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{x-a}$.

Firstly, when x=a, the expression $\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{x-a}$ assumes the form as$\dfrac{0}{0}$.

So, we will let$Z=\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{x-a}$.

If we use the formula$\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{n}^{a}}-{{a}^{n}}}{n-a}=n{{a}^{n-1}}$, then also Z will not show the form$\dfrac{0}{0}$as mentioned.

So, we need to simplify, that means,

Now, we will add 2 in the denominator, but we will not change the denominator so we will subtract 2 also, that means, we get,

$\Rightarrow Z=\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{2+x-(a+2)}$

Now, we will let 2+x=y and a+2=k, as$x\to a;y\to k$, we get,

$\Rightarrow Z=\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{y}^{5/2}}-{{k}^{5/2}}}{y-k}$

Now, we will use the formula$\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{n}^{a}}-{{a}^{n}}}{n-a}=n{{a}^{n-1}}$, we get,

$\Rightarrow Z=\dfrac{5}{2}{{k}^{\dfrac{5}{2}-1}}$

$\Rightarrow Z=\dfrac{5}{2}{{k}^{\dfrac{3}{2}}}$

Now, we will place the value of k in the above equation, we get,

$\Rightarrow Z=\dfrac{5}{2}{{(a+2)}^{\dfrac{3}{2}}}$

**Therefore, after evaluation of$\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{x-a}$, we get, $\dfrac{5}{2}{{(a+2)}^{\dfrac{3}{2}}}$.**

**Note:**

You just need to note for the evaluation for the above question we need to check if it is in the form of $\dfrac{0}{0}$, if it is not then we will continue to simplify. Here, in this question we used the formula $\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{n}^{a}}-{{a}^{n}}}{n-a}=n{{a}^{n-1}}$ in the simplification.

Recently Updated Pages

what is the correct chronological order of the following class 10 social science CBSE

Which of the following was not the actual cause for class 10 social science CBSE

Which of the following statements is not correct A class 10 social science CBSE

Which of the following leaders was not present in the class 10 social science CBSE

Garampani Sanctuary is located at A Diphu Assam B Gangtok class 10 social science CBSE

Which one of the following places is not covered by class 10 social science CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

How do you graph the function fx 4x class 9 maths CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference Between Plant Cell and Animal Cell

Why is there a time difference of about 5 hours between class 10 social science CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Draw a labelled sketch of the human eye class 12 physics CBSE